Corporate Governance and Business Performance. Theories and Evidence about Corporate Governance - Aws AlHares; Gerard Dominic (Corporate Governance and Business Performance. Theories and Evidence about Corporate Governance, 2021)
This book dealt with corporate governance. The contributions by the authors include laws, regulations, corporate management, legislation, shareholders, Corporate Regulation, performance remuneration, London Stock Exchange, accountability, non-compliant business, financial structure, cashflows, agency costs, institutional shareholders, tax benefits, financial repolting, corporate control market, econometric model, economic gains, quasi-equity, securities, stock market, productivity, managerial agency, public firms, influence management, egalitarian approach, Anglo-American system, Glass-Steagall law, Anglo-Saxon system, social relations, real estate portfolios, bubble economy, financial system, financial encumbrance, trade, money markets, privatization, fragmented control, monopoly, foreign exchange. This book contains various materials suitable for students, researchers and academicians.